Knowledge, attitudes, and experiences of ECT among psychiatric trainees and early career psychiatrists in Iran - Hosseini, Seyedeh Reihaneh; Shalbafan, Mohammadreza; Ghannadi, Farnaz; Boroon, Mahsa; Askari, Sanaz; Nazeri Astaneh, Ali; Sayed Mirramazani, Mostafa; Tapoi, Cristiana; Pinto da Costa, Mariana (Frontiers in Psychiatry, 2025)
ObjectiveThis study aimed to examine the experiences of psychiatric trainees and early career psychiatrists in Iran with Electroconvulsive Therapy (ECT).MethodsA cross-sectional survey, employing a 36-item questionnaire was conducted in Iran from March to November 2023. The survey targeted psychiatric trainees and early career psychiatrists, assessing ECT availability, training experiences, knowledge and attitudes.Results173 responses were received. The majority of respondents were female (79.2%) and had experience in inpatient settings. About 63.0% reported ECT availability in their institutions, with 89.0% confirming the presence of specialised ECT centers within 100 km. Training in ECT was widely reported (96.5%), with 77.4% administering ECT to 10 or more patients during psychiatry training. However, only 55.5% were familiar with national ECT guidelines, and even fewer knew about international recommendations. Attitudes toward ECT were largely positive, with 86.2% agreeing on its effectiveness and 77.5% willing to recommend it to patients. ECT services were less frequently available in institutions where ECPs were employed compared to institutions where trainees were undergoing their psychiatry training. Confidence in ECT knowledge varied, with 52.6% feeling confident in their understanding, and 75.7% expressed interest in additional training.ConclusionsThe study highlights a gap between ECT training and confidence among Iranian psychiatrists. Positive attitudes toward ECT and a high level of interest in further training underscore the need for enhanced educational programs and the standardisation of guidelines. Addressing stigma and policy gaps is crucial for improving ECT access and utilisation.